Recent advances of sustainable and recyclable polymer materials from renewable resources - Ting Luo; Yun Hu; Meng Zhang; Puyou Jia; Yonghong Zhou (Resources Chemicals and Materials)
With the increasing consumption of non renewable resources such as oil, the traditional polymer manufacturing industry that relies on fossil resources is facing unprecedented challenges. The design, synthesis, and recycling of renewable and environmentally friendly bio-based polymers as alternatives to petroleum based polymers have become hot topics in research and industrial fields. Biomass has been used as a raw material to design and synthesize closed-loop recyclable polymers, which is of great significance in addressing the waste of resources and negative impact on the environment in the traditional polymer preparation process. This review summarized recent advances in the design, synthesis, and properties of closed-loop recyclable bio-based polymers, focusing on the sustainability and recyclability of bio-based materials, followed by a brief discussion of the potential applications of closed-loop recyclable bio-based polymers in emerging applications such as 3D printing and friction electric nanogenerators. In addition, perspectives and recommendations for future research on closed-loop recyclable bio-based polymers were presented.